2022
DOI: 10.1038/s41386-022-01416-z
|View full text |Cite
|
Sign up to set email alerts
|

Opioid antagonism in humans: a primer on optimal dose and timing for central mu-opioid receptor blockade

Abstract: Non-human animal studies outline precise mechanisms of central mu-opioid regulation of pain, stress, affiliation and reward processing. In humans, pharmacological blockade with non-selective opioid antagonists such as naloxone and naltrexone is typically used to assess involvement of the mu-opioid system in such processing. However, robust estimates of the opioid receptor blockade achieved by opioid antagonists are missing. Dose and timing schedules are highly variable and often based on single studies. Here, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…One has to be aware that after a single high naloxone dose, renarcotization still might occur. 6,26 For example, simulations of naloxone receptor blockade (without an opioid present) indicate that µ-opioid receptor blockade greater than 90% lasts no longer than 30 min after 0.01 mg/kg naloxone bolus and about 1 h after a 10- to 15-fold higher dose. 26 When moderate- to high-affinity opioids are on board, the naloxone receptor blockade will be shorter due to the competition with the higher-affinity opioid at the receptor.…”
Section: Receptor Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…One has to be aware that after a single high naloxone dose, renarcotization still might occur. 6,26 For example, simulations of naloxone receptor blockade (without an opioid present) indicate that µ-opioid receptor blockade greater than 90% lasts no longer than 30 min after 0.01 mg/kg naloxone bolus and about 1 h after a 10- to 15-fold higher dose. 26 When moderate- to high-affinity opioids are on board, the naloxone receptor blockade will be shorter due to the competition with the higher-affinity opioid at the receptor.…”
Section: Receptor Kineticsmentioning
confidence: 99%
“…6,26 For example, simulations of naloxone receptor blockade (without an opioid present) indicate that µ-opioid receptor blockade greater than 90% lasts no longer than 30 min after 0.01 mg/kg naloxone bolus and about 1 h after a 10-to 15-fold higher dose. 26 When moderate-to high-affinity opioids are on board, the naloxone receptor blockade will be shorter due to the competition with the higher-affinity opioid at the receptor. 27 (3) Opioids that Dissociate Slowly from the Receptor (K OFF 0.001 s −1 or Less) High-affinity opioids with slow receptor dissociation kinetics are used in clinical practice and often found in illegal substances.…”
Section: ) Long-acting Potent Opioids With Low-to-intermediate Affini...mentioning
confidence: 99%
“…Despite these earlier studies, robust estimates for the opioid receptor blockade by opioid antagonists were not available until recently. Trøstheim et al [ 41 ] reviewed the existing positron emission tomography data for a detailed analysis of central opioid receptor blockade after opioid antagonism. Positron emission-based techniques can be used to estimate receptor blockade, because antagonist drugs prevent accumulation of the radiotracer in the brain [ 41 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…This raises the question of what is the minimally effective NTX plasma level needed to produce its therapeutic effect, including blockade of opioid effects. Although this could be complicated by the nonlinear relationship between plasma levels to μ-receptor binding, especially with oral NTX administration, we do not expect it to be significant with a sustained-release formulation of NTX 19,20 . Previous studies have shown blockade of the effects of moderate doses of opioids administered in the human laboratory for most individuals for 28 days after XR-NTX administration at doses of 75, 150, or 300 mg IM 21 and 192 and 384 mg subcutaneously (SC), 22 whereas clinical experience suggests that some patients begin to experience craving and possibly opioid effects around 21 days after XR-NTX 380-mg IM administration 23 .…”
mentioning
confidence: 94%
“…Although this could be complicated by the nonlinear relationship between plasma levels to μ-receptor binding, especially with oral NTX administration, we do not expect it to be significant with a sustained-release formulation of NTX. 19,20 Previous studies have shown blockade of the effects of moderate doses of opioids administered in the human laboratory for most individuals for 28 days after XR-NTX administration at doses of 75, 150, or 300 mg IM 21 and 192 and 384 mg subcutaneously (SC), 22 whereas clinical experience suggests that some patients begin to experience craving and possibly opioid effects around 21 days after XR-NTX 380-mg IM administration. 23 These studies combined demonstrate that the ability of NTX to block opioid agonist effects is dependent on the NTX dose administered, time since NTX dose administration, and dose of opioid agonist used.…”
mentioning
confidence: 99%